Cross-allergenicity of crustacean and the edible insect Gryllus bimaculatus in patients with shrimp allergy. (February 2019) - Kamemura, Norio; Sugimoto, Mayumi; Tamehiro, Norimasa; Adachi, Reiko; Tomonari, Sayuri; Watanabe, Takahito; Mito, Taro
Highlights: Cross-allergenicity occurs between field cricket ( Gryllus bimaculatus ) and shrimp. Binding of shrimp-specific IgE was dose-dependently inhibited by Gryllus allergen. The major allergen in shrimp and Gryllus was determined to be tropomyosin. Abstract: Food scarcity is a serious problem for many developing as well as developed countries. Edible insects have attracted attention recently as a novel food source. Crickets are especially high in nutritional value and easy to breed and harvest. In this study, we evaluated the risk of allergic reactions associated with cricket consumption in individuals with crustacean allergy. We evaluated food allergy risk in the consumption of Gryllus bimaculatus (cricket) in patients with shrimp allergy, using enzyme-linked immunosorbent assay (ELISA) and IgE crosslinking-induced luciferase expression assay (EXiLE). Sera from individuals with shrimp allergy (positive for shrimp-specific IgE by ImmunoCAP (>0.35 UA/mL; n = 9) or without shrimp allergy (negative for shrimp-specific IgE; n = 6) were obtained. There was a strong correlation between shrimp- and Gryllus -specific IgE levels obtained by ELISA ( rs = 0.99; P < 0.001). The binding of shrimp-specific IgE on shrimp allergen was dose-dependently inhibited by Gryllus allergen (0–1.0 mg/mL). There was a strong correlation between shrimp- and Gryllus -specific IgE responses, as assessed by EXiLE assays ( rs = 0.89; P < 0.001). We determined that a protein of approximately 40 kDa reacted with the positive, but not negative, sera for shrimp-specific IgE by ImmunoCAP. Liquid chromatography-tandem mass spectrometry (LC–MS/MS) analysis identified the major allergen in shrimp and Gryllus to be tropomyosin. Our data suggest that the cricket allergen has the potential to induce an allergic reaction in individuals with crustacean allergy. Therefore, allergy risk and shrimp-specific IgE levels should be considered before consumption of cricket meal.